The Relationship between Knowledge and Preparedness to Deal with Dense Residential Fires in Antang Village, Manggala District, Makassar City - Muh. Yunus; Alamsyah Alamsyah; Ramadhan Husni Putri; Tut Handayani; Ade Rendra Kurniawan (International Journal Of Health Science, 2025)
Residential fires are one of the disasters that often occur in densely populated areas and have the potential to cause major losses both in terms of safety and public health. The level of public knowledge is an important factor that affects preparedness in dealing with these situations. This study aims to analyze the relationship between the level of community knowledge and preparedness to deal with residential fires in Antang Village, Manggala District, Makassar City. The research design used was cross-sectional with a total of 67 respondents selected through simple random sampling technique. Data was collected using a questionnaire that had been tested for validity and reliability, then analyzed using the Chi-Square test with a significance level of 0.05. The results showed a significant relationship between the level of community knowledge and preparedness to deal with residential fires (p = 0.000). In conclusion, the higher the level of public knowledge, the better their preparedness in dealing with fire disasters. Efforts to improve education and training on fire simulations are needed periodically to strengthen community preparedness.